Identification of Contributing Factors of Household Food Insecurity Among Indigenous People (Orang Asli) in Peninsular Malaysia Under Cash Economy: A Qualitative Approach - Leh Shii, Law; Norhasmah, Sulaiman; Wan Ying, Gan; Siti Nur’Asyura, Adznam (UPM Press, 2025)
The Orang Asli (OA) were recognised as a marginalised group with their disadvantageous living conditions exposing them to household food insecurity. This qualitative study was conducted to explore the potential contributing factors linked with the difficulties experienced by OA households of Peninsular Malaysia in purchasing enough food under a cash-based economy. Materials and methods: This qualitative study (case study design) involved 61 mothers of three main OA ethnic groups (Senoi, Proto-Malay, and Negrito) from three purposively selected districts across Pahang, Perak, and Kelantan states in Peninsular Malaysia. Semi-structured in-depth interviews were conducted with the aid of controlled interview protocol to gather their opinions pertaining to their hardship in purchasing food from markets. Thematic analysis was performed manually during data analysis. Results: The findings revealed the varying influence of the following factors on household food insecurity: sociodemographic factors (low pay and impermanent job, care for small children, lack of transport, and large-sized households), economic factors (the high price of petrol, non-food necessities and transport fares) and geographical factors (lack of grocery shops within walking distance, inconsistent operating hours of nearby grocery shops, higher prices at nearby grocery shops, nearby grocery shops not fulfilling demand and dissatisfactory road conditions). Conclusion: It was concluded that local authorities should acknowledge the perceived contributing factors towards household food insecurity among the OA to understand more comprehensively the needs of the affected communities from their own point of view so that effective strategies can be planned in order to ultimately reduce their burden.